Fluorescence-Based Analysis of Noncanonical Functions of Aminoacyl-tRNA Synthetase-Interacting Multifunctional Proteins (AIMPs) in Peripheral Nerves - Muwoong Kim (Materials, 2019)
Aminoacyl-tRNA synthetase-interacting multifunctional proteins (AIMPs) are auxiliary factors involved in protein synthesis related to aminoacyl-tRNA synthetases (ARSs). AIMPs, which are well known as nonenzymatic factors, include AIMP1/p43, AIMP2/p38, and AIMP3/p18. The canonical functions of AIMPs include not only protein synthesis via multisynthetase complexes but also maintenance of the structural stability of these complexes. Several recent studies have demonstrated nontypical (noncanonical) functions of AIMPs, such as roles in apoptosis, inflammatory processes, DNA repair, and so on. However, these noncanonical functions of AIMPs have not been studied in peripheral nerves related to motor and sensory functions. Peripheral nerves include two types of structures: peripheral axons and Schwann cells. The myelin sheath formed by Schwann cells produces saltatory conduction, and these rapid electrical signals control motor and sensory functioning in the service of survival in mammals. Schwann cells play roles not only in myelin sheath formation but also as modulators of nerve degeneration and regeneration. Therefore, it is important to identify the main functions of Schwann cells in peripheral nerves. Here, using immunofluorescence technique, we demonstrated that AIMPs are essential morphological indicators of peripheral nerve degeneration, and their actions are limited to peripheral nerves and not the dorsal root ganglion and the ventral horn of the spinal cord.